The Attributes, Purpose, Boundaries, and Effects: Gpt-3 - T. Jayasri, Sk. Heena, U. Amulya, M Akshitha Laasya, B. Sonia (Mathematical Statistician and Engineering Applications, 2023)
In this post, we address Questions that are both treatable and irrevocable is, questions that can allow to determine the kind of determinant of the solution, their characteristics. Then, using the prior distinction as an analysis, we provide GPT-3, an automatic third-generation language model using deep learning to create sentences that are human-like. We broaden the scrutiny to give three tests which are based on ethical, mathematical, and semantics issues, we demonstrate that GPT-3 is not intended to clear any one of them. This serves as a warning that GPT-3 does not behave as it should and that Any perception of GPT-3 as the very first milestone toward the emergence of a general type of artificial intelligence is incorrect essentially science fiction based on a lack of knowledge. We wrap off by highlighting some of the key drawbacks of the industrialization of efficient, low-cost production of high-quality semantic artefacts.